CONTINUOUS QUALITY IMPROVEMENT IN PROCESS - García P., Manuel (2003)
The current approach of quality within organizations has changed from the securing level to the continuous improvement level. The NTP-ISO 9000:2001 Series of Norms can confirm this and show how, unlike its previous version, it emphasizes on a continuous improvement in process quality.